Determine the Morphological and Etiological Types of Anaemia that are Common in Children Between the Ages of 3 and 15 Years (International Journal of Food and Nutritional Sciences, 2022)
Background: A serious issue with world health is anaemia. An accurate morphological and etiological subtyping of anaemia can help clinicians manage patients more effectively. Red blood cell and platelet indices, which can now be obtained from widely used blood cell counters in the laboratory, along with peripheral smear analysis, aid in the accurate classification of anaemia. Aim and Objective: To detect the morphological and etiological types of anaemia prevalent among children in the age group of 3 years to 15 years.Methodology: This study was conducted in the haematology wing of Pathology Department, Santosh Medical College & hospital. It was a descriptive and cross sectional study done over a period of November 2018 to December 2019 with 300 cases. Patients' venous blood samples were taken in EDTA vacutainers while requests for complete blood counts and complete haemograms were being sent by various clinical departments. Daily quality checks were done as per standard protocols.Result: Out of 300 cases studied, 147 (49%) were males and 153 (51%) were females. Mild degree of anaemia was more prevalent in school going children than in pre-school children, while severe anaemia was equally present in both preschool and school going children. The most common morphological type of anaemia was microcytic hypochromic anemia (57.33 %)Conclusion: Children need to be screened early for anaemia and related disorders because they are the group most at risk for nutritional deficiencies. Utilizing prenatal diagnostic methods and spotting these illnesses early would guarantee enormous advantages and pain relief.